Direct molecular detection of SRY gene from unamplified genomic DNA by metal-enhanced fluorescence and FRET - Brouard, Danny (2013)
A biosensor based on a cationic polymer and metal@silica core–shell nanoparticles is demonstrated for the rapid identification of the SRY gene from unamplified human genomic DNA. By amplifying the fluorescence signal triggered by the capture of target molecules, this biosensor avoids the added complexity of enzyme-based chemical amplification, makes genotyping assays faster and less costly and could have important applications in various areas of health sciences.